Surgical site infection prevention bundle in elective colorectal surgery. (April 2022) - Dixon, L.K.; Biggs, S.; Messenger, D.; Shabbir, J.
Summary: Objective: Surgical Site Infections (SSIs) are responsible for a significant economic burden as well as intangible costs suffered by the patient, with up to 60% deemed preventable. Colorectal patients are disproportionally affected by SSI due the risk of wound contamination with bowel content. We aimed to reduce the rate of superficial SSI after elective colorectal surgery using a bundle of evidence-based interventions. Methods: An SSI prevention bundle was implemented in elective colorectal surgery, comprised of triclosan-coated sutures, 2% chlorhexidine skin preparation and use of warmed carbon dioxide (CO2 ) during laparoscopic procedures. The SSI reduction strategy was prospectively implemented and compared with historical controls. Our primary outcome measure was the overall rate of superficial SSI. Centres for Disease Control and Prevention criteria, which use microbiological evidence in conjunction with clinical features were used as the definition of SSI. Results: The overall SSI rate was 27.4% in the pre-bundle group ( N = 208) and 12.5% in the patients who received the SSI prevention bundle ( N = 184) (adjusted odds ratio 0.38; confidence interval 0.21–0.67; P <0.001). The median time to SSI diagnosis was postoperative day 8. Overall patient length of stay (LOS) was unchanged from six days at baseline following implementation of the bundle. Conclusions: We have shown successful implementation of an SSI prevention bundle which has reduced superficial SSI rate. We recommend this SSI prevention bundle becomes standard practice in elective colorectal surgery and plan to extend the bundle to emergency general surgery.